Evaluasi Penyelenggaraan Webinar: Strategi UMKM Korea Selatan Bertahan Dalam Pandemi COVID-19 - Nadya Megawati Rachman (Cendekia Niaga, 2020)
One of the economic sectors that has been significantly affected by the COVID-19 pandemic in Indonesia is the middle and lower class businesses, which are often referred to as Medium, Small and Micro Enterprises (MSMEs). The Trade Education and Training Center, has an important role in being able to contribute to the wider community, by providing information and knowledge and new enthusiasm in facing this pandemic, one of which is for MSMEs in Indonesia by holding various trainings and seminars which are held online (webinars) which accessible to all MSME players in Indonesia. Pusdiklat Trade held a webinar with the theme "Strategies for South Korean MSMEs to Survive the COVID-19 Pandemic" with resource persons the Head of ITPC (Indonesia Trade Promotion Center) Busan - South Korea using the Kudagang LMS (Learning Management System). The purpose of this study was to evaluate the implementation of knowledge sharing using the distance learning method (e-learning) by utilizing the Kudagang LMS using the CIPP (Context, Input, Process and Product) evaluation approach. The research method used is quantitative methods through surveys using questionnaires and qualitative descriptive approaches through scientific literature review. The results showed that the average score of the participants' evaluation of the webinar was in the good and satisfying category. Although there are still several components that need to be improved, this webinar activity is feasible to continue with different materials and sources and is targeted at participating stakeholders from various stakeholders related to the duties and functions of the Trade Education and Training Center, both ASN and non ASN as centers of excellence for trade people in Indonesia.